Development and Initial Validation of the Willingness to Compromise Scale - WEE, Serena (Institutional Knowledge at Singapore Management University, 2013)
This study introduced an individual difference construct of willingness to compromise and examined its implications for understanding and predicting career-related decisions in work settings. In Study 1 (N = 53), critical incidents of career decisions were analyzed to identify commonalities across different types of career-related compromises. In Study 2 (N = 171), an initial 17-item scale was developed and revised. In Study 3 (N = 201), the convergent and criterion-related validity of the scale was examined in relation to specific personality traits, regret, dealing with uncertainty, career adaptability, and a situational dilemma task. Willingness to compromise was negatively related to neuroticism, and positively related to dealing with uncertainty, openness to experience, and career adaptability; it also predicted responses to the situational dilemma task. Results provided support for the reliability and validity of the scale.